Urine colour after radical prostatectomy predicts urinary leakage at the vesicourethral anastomosis - Schöppler, Gita (Scandinavian journal of urology and nephrology, 2012)
Objective: The aim of this investigation was to determine whether postoperative urine colour could be used as a predictor for the presence or absence of a :urinary leakage at the vesicourethral anastomosis after open radical prostatectomy. Material and methods. In this prospective study, the urine colour of 223 patients who underwent open radical prostatectomy due to histologically proven localized prostate cancer was assessed macroscopically and microscopically on postoperative day (POD) 6, 7 and 8. All patients underwent evaluation of perianastomotic extravasation by retrograde cystography on POD 8. Baseline characteristics included age; prostate-specific antigen; prostate volume; tumour, node, metastasis classification; and Gleason score. Results. The urine colour was a highly significant predictor for perianastomotic extravasation in cystography when it was red on POD 6, 7 and 8. The sensitivity and specificity of urine colour as a predictor for extravasation were 71.4% and 83.2% on POD 6, 71.4% and 85.8% on POD 7, and 81.8% and 90.9% on POD 8, respectively, with a clear or slightly ensanguined urine colour. The negative and positive predictive values were 98.6% and 81.8%, respectively. Conclusion. A cystography can be omitted if the patient demonstrates a clear urine colour on POD 8, without an increased risk of missing a perianastomotic extravasation.
Published online: 21 May, 2012
Gesehen am 16.07.2018